HLA class I hyper-expression unmasks beta cells but not alpha cells to the immune system in pre-diabetes - Benkahla, Mehdi A.; Sabouri, Somayeh; Kiosses, William B.; Rajendran, Sakthi; Quesada-Masachs, Estefania; von Herrath, Matthias G. (Journal of autoimmunity, 2021)
Human leukocyte antigens of class-I (HLA-I) molecules are hyper-expressed in insulin-containing islets (ICI) of type 1 diabetic (T1D) donors. This study investigated the HLA-I expression in autoantibody positive (AAB+) donors and defined its intra-islet and intracellular localization as well as proximity to infiltrating CD8 T cells with high-resolution confocal microscopy. We found HLA-I hyper-expression had already occurred prior to clinical diagnosis of T1D in islets of AAB+ donors. Interestingly, throughout all stages of disease, HLA-I was mostly expressed by alpha cells. Hyper-expression in AAB+ and T1D donors was associated with intra-cellular accumulation in the Golgi. Proximity analysis showed a moderate but significant correlation between HLA-I and infiltrating CD8 T cells only in ICI of T1D donors, but not in AAB+ donors. These observations not only demonstrate a very early, islet-intrinsic immune-independent increase of HLA-I during diabetes pathogenesis, but also point towards a role for alpha cells in T1D. •HLA-I was hyperexpressed in autoantibody positive (AAB+) patients prior to clinical diagnosis of T1D.•HLA-I was mostly expressed by alpha cells irrespective of disease status.•In islets of AAB+ and T1D donors, HLA-I accumulates in the Golgi compartment.•A significant correlation between HLA-I and infiltrating CD8 T cells in insulin-containing islets of T1D donors.